The Impact of China's Paired Assistance Policy on the COVID-19 Crisis—An Empirical Case Study of Hubei Province - Huang, Rui; Yao, Xiantao; Chen, Zhishan; Li, Wan; Yan, Haobo (Frontiers in Public Health, 2022)
To control the coronavirus pandemic (COVID-19), China implemented the Paired Assistance Policy (PAP). Local responders in 16 cities in Hubei Province were paired with expert teams from 19 provinces and municipalities. Fully supported by the country’s top-down political system, PAP played a significant role in alleviating the COVID-19 pandemic in Hubei Province and China as a whole. In this study, we examined PAP using a two-way fixed effects model with the cumulative number of medical support personnel and cumulative duration as measurements. The results show personnel and material support played an active role in the nation’s response to the COVID-19 public health crisis.